A study on the status of saltwater intrusion in the coastal hard rock aquifer of South India - Singaraja, C.; Chidambaram, S.; Anandhan, P.; Prasanna, Mohan Viswanathan; Thivya, C.; Thilagavathi, R. (Springer, 2015)
Groundwater of the coastal regions represents a fragile environment. A study has been attempted in the hard rock aquifer of the south-eastern part of India. A total of 135 groundwater samples were collected and analysed for major cations and anions. The domination of cations and anions was in the order of Na+ > Ca2+ > Mg2+ > K+ for cations and Cl− > HCO3− > SO42− > H4SiO4 > NO3− > PO4− > F− in anions. The water is neutral to alkaline in nature with pH ranging from 6.30 to 9.20 with an average of 7.57. The ions analysed were used for standard plots, ratio of different ions and correlation between them helped to evaluate the active hydrogeochemical process and extent of saltwater intrusion in the coastal aquifer. The electrical conductivity (EC) contour shows that the groundwater quality is poor along the coast due to saltwater intrusion. The Piper and chadda’s plot shows that most of the groundwater samples fall on Na–Cl water type may be due to saltwater intrusion in the eastern part study area. The ratios of Cl−/HCO3− ranged between 0.24 and 152.50 and have strong positive relationship with Cl− concentrations; it was found that about 30 % of the groundwater samples were strongly affected by the saline water in the study area. The Na+/Cl− ratios ranged from 0.20 to 3.73, and most of the groundwater samples fall close to the contamination region. Agricultural and salt pan land use pattern decrease the water quality due to impact of anthropogenic processes and seawater intrusion. Statistical analysis was also used to obtain the objectives, and it was found that the seawater intrusion is the major factor controlling the groundwater chemistry followed by other factors such as weathering and fertiliser impact.